Complete OS X Mavericks - Harvell, Ben, 1981- (Teach yourself visually., 2014)
A deep dive into OS X Mavericks If you want to quickly cover the basics of Apple's new operating system, OS X Mavericks, and then delve deeper into the topic, this is the book for you. Using clear, step-by-step screenshots, Teach Yourself VISUALLY Complete OS X Mavericks shows you how to tackle not only beginning but also intermediate and more advanced functions. Two-page, side-by-side lessons break big topics into smaller bits, and you'll find helpful sidebars with plenty of practical tips and tricks. If you're a visual learner looking for enhanced coverage of OS X Mave.